Environment And Climate Change in Sri Lanka: A Study in Light of the International Legal Framework - Balasooriya, B.C.L. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Sri Lanka, a tropical island nation highly vulnerable to climate-induced disasters, faces a critical challenge in legally integrating environmental protection with rapid development. This study undertakes a comparative, multi-disciplinary legal analysis of the country’s framework for addressing environmental degradation and climate change impacts. The research is vital as climate risks threaten Sri Lanka’s socio-economic stability, food security, and vulnerable coastal communities. A rigorous legal review is essential to assess the effectiveness, enforceability, and constitutional grounding of current laws against progressive international standards. These domestic legal instruments are critically compared with Sri Lanka’s obligations under international law, including the United Nations Framework Convention on Climate Change (UNFCCC) and the Paris Agreement ,the Rio Declaration on Environment and Development and the Sustainable Development Goals. The study identifies a significant gap in comprehensive scholarship examining the coherence and enforceability of Sri Lanka’s dualist legal system in implementing international climate commitments. In particular, the constitutional status of climate-related rights and the incorporation of principles such as intergenerational equity into the regulatory mechanisms of the NEA remain underexplored. Preliminary findings indicate that the National Environment Act (NEA) provides a robust framework for general pollution control and project approval (EIA), but its direct provisions for climate change are fragmented and often policy-driven. Constitutional provisions are largely directive rather than justiciable rights, requiring judicial activism for environmental justice. While Sri Lanka’s updated (Nationally Determined Contribution)NDCs under the UNFCCC demonstrate ambition, their necessary legal underpinning is often lacking, highlighting weak domestic implementation and the need for a comprehensive Climate Change Act. The study concludes that is imperative to transition from a policy-centric to a legally-binding framework, enhancing accountability for climate action, strengthening institutional capacity for SDG implementation, and fully domesticating principles of climate justice and the polluter pays principle.
Keywords: Climate justice; National environment act; UNFCCC; Legal reform; Intergenerational equity